2022
DOI: 10.3390/biomedicines10092324
|View full text |Cite
|
Sign up to set email alerts
|

The JAK1/2 Inhibitor Baricitinib Mitigates the Spike-Induced Inflammatory Response of Immune and Endothelial Cells In Vitro

Abstract: The purpose of this study was to examine the effect of the JAK-STAT inhibitor baricitinib on the inflammatory response of human monocyte-derived macrophages (MDM) and endothelial cells upon exposure to the spike S1 protein from SARS-CoV-2. The effect of the drug has been evaluated on the release of cytokines and chemokines from spike-treated MDM, as well as on the activation of endothelial cells (HUVECs) after exposure to conditioned medium collected from spike-activated MDM. Results obtained indicate that, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
2
10
1
Order By: Relevance
“…Since this transcription factor is a downstream target gene of STAT1 in the JAK/STAT signaling pathway, the molecular mechanisms underneath cytomix-dependent cell growth arrest were investigated by employing the JAK1/2 inhibitor baricitinib ( Figure 5 ). To this concern, we have also recently demonstrated that the exposure of A549 cells to conditioned medium from spike S1-activated human macrophages triggers IRF1 expression through the JAK1/2–STATs axis [ 33 , 34 ]. Results shown in Panel A demonstrated that the exposure to IFNγ + TNFα caused the phosphorylation of STAT1 in both WT and IRF1 KO cells, an effect completely prevented, as expected, by baricitinib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this transcription factor is a downstream target gene of STAT1 in the JAK/STAT signaling pathway, the molecular mechanisms underneath cytomix-dependent cell growth arrest were investigated by employing the JAK1/2 inhibitor baricitinib ( Figure 5 ). To this concern, we have also recently demonstrated that the exposure of A549 cells to conditioned medium from spike S1-activated human macrophages triggers IRF1 expression through the JAK1/2–STATs axis [ 33 , 34 ]. Results shown in Panel A demonstrated that the exposure to IFNγ + TNFα caused the phosphorylation of STAT1 in both WT and IRF1 KO cells, an effect completely prevented, as expected, by baricitinib.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we demonstrated that the exposure of A549 cells to conditioned medium (CM) obtained from SARS-CoV-2-activated human macrophages caused proliferative arrest [ 33 ]; by analyzing the cytokine content of this conditioned medium, we concluded that the IFNγ–IRF1 axis likely plays a central role in the induction of this cytostatic effect [ 34 ]. Based on these findings, the present study aimed to deepen this issue by assessing the contribution of single and combined inflammatory cytokines IFNγ, TNFα, IL-1β and IL-6 on growth arrest and on the secretory phenotype of A549 alveolar epithelial cells; in addition, we clarified the role of IRF1 by taking advantage of A549 cells knockout for this transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that the exposure of alveolar A549 cells to conditioned medium (CM) from spike S1-activated macrophages causes the activation of the epithelial cells; the reason is the massive presence of cytokines released from treated macrophages that, in turn, provokes a further release of inflammatory mediators from epithelial cells [ 18 , 24 ]. Given the relevance of the epithelial alveolar damage in COVID-19 disease, we examine here whether this treatment causes, in addition, signs of cell injury.…”
Section: Resultsmentioning
confidence: 99%
“…The JAK/STAT pathway is currently recognized as a signalling mechanism central to the response and secretion of cytokines and chemokines in COVID-19 [ 24 , 35 , 36 ]; thus, it is now generally accepted that targeting JAKs represents a valid therapeutic strategy for the treatment of the disease [ 37 ]. Among the JAK-STAT inhibitors, baricitinib proved effective in preventing the progression to a severe form of COVID-19 with reduced hospitalization and mortality [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation